Another Bretton Woods reform moment: Let us look seriously at the clearing union - Jan A. Kregel (Levy Economics Institute of Bard College, 2021)
This policy brief explores a route to remaking the international financial system that would avoid the contradictions inherent in some of the prevailing reform proposals currently under discussion. Senior Scholar Jan Kregel argues that the willingness of central banks to consider electronic currency provides an opening to reconsider a truly innovative reform of the international financial system, and one that is more appropriate to a digital monetary world: John Maynard Keynes's original clearing union proposal. Kregel investigates whether such a clearing system could be built up from an already-existing initiative that has emerged in the private sector. He analyzes the operations of a private, cross-border payment system that could serve as a real-world blueprint for a more politically palatable equivalent of Keynes's international clearing union.
Keywords: 330; Bretton-Woods-System; Elektronisches Geld; Internationales Finanzsystem; Keynesianismus